Implementation of the Scaffolding Method in Improving Adab Learning Using Social Media at SMK Negeri 1 Raya Simalungun Implementation of the Scaffolding Method in Improving Adab Learning Using Social Media at SMK Negeri 1 Raya Simalungun - Siregar, Marlina; Muriati, Dewi Sri; Maisyarah, Rini; Sari, Maya; Nasution, Alamsyah (MANDAILING GLOBAL EDUKASIA, 2025)
The use of social media by students is increasing, but without proper understanding, it can have negative impacts, especially in terms of manners and ethics. This study aims to apply the scaffolding method to improve students' understanding of manners in using social media at SMK Negeri 1 Raya Simalungun. The scaffolding method is a learning approach that provides gradual guidance until students are able to learn independently. This study uses the classroom action research (CAR) method with stages of planning, implementation, observation, and reflection. The results of the study showed that the application of the scaffolding method effectively improved students' understanding and awareness of ethics on social media. This improvement can be seen from changes in students' attitudes and habits in communicating more politely, responsibly, and wisely in using social media. Thus, the scaffolding method can be an effective learning strategy in improving understanding of manners in using social media among SMK students